Doubly‐Resonant Enhancement of Second Harmonic Generation from a WS2 Nanomesh Polymorph with a Modified Energy Landscape. Issue 6 (10th May 2021) - Murphy, Alexander W. A.; Liu, Zichen; Gorbach, Andrey V.; Ilie, Adelina; Valev, Ventsislav K.
Abstract: Although transition metal dichalcogenides (TMDs, e.g., WS2, WSe2, MoS2, MoSe2 ) have emerged as highly promising 2D materials for nonlinear optics, they are limited by intrinsically small light‐matter interaction length and (typically) flat‐lying geometries. The first hyperspectral multiphoton analysis of a tridimensional webbed network of densely‐packed stacks (of 1–5 layers) of twisted and/or fused 2D nanosheets of WS2, referred to as "nanomesh", is presented here. The optical second harmonic generation (SHG) is mapped across the three characteristic spectral features (A, B, and C) and two‐photon luminescence and third harmonic generation signatures are established. Compared to flat‐lying WS2 layers, the nanomesh is highly efficient, broadband, and robust against degradation (with main enhancement originating from the C feature, spreading from 850 to 1100 nm), and scalable in terms of growth. The origin of these spectral differences is assigned to hotspots, whose location changes depending on the wavelength of illumination. The main SHG enhancements result from double resonances in an energy landscape modified by in‐built defects (e.g., vacancies and their passivated variants, or grain boundaries) that induce intra‐bandgap energy levels. These characteristics establish the nanomesh as a prime candidate for integration into quantum optical technologies, such as miniaturized devices on chip. Abstract : Large second harmonic generation (SHG) is reported from densely‐spaced, randomly‐arranged, 3D‐networks of a WS2 polymorph (referred to as "nanomesh"). The enlargement is attributed to doubly resonant SHG at the broad C spectral feature of the transition metal dichalcogenide.